CXCL16/CXCR6 interaction promotes endometrial decidualization via the PI3K/AKT pathway. Issue 3 (March 2019) - Mei, Jie; Yan, Yuan; Li, Shi-Yuan; Zhou, Wen-Jie; Zhang, Qun; Li, Ming-Qing; Sun, Hai-Xiang
Abstract : Decidualization renders the endometrium transiently receptive to an implanting blastocyst although the underlying mechanisms remain incompletely understood. The aim of this study was to determine the role of chemokine CXCL16 and its receptor CXCR6 in the decidualization during pregnancy. Here, the expression of CXCL16 was investigated in endometrial tissues, decidua and placenta in this study. Compared with endometrial tissue, protein expression of CXCL16 was significantly higher in tissues from the fertile control samples, especially in villus. Meanwhile, the primary trophoblast cells and decidual stromal cells (DSCs) secreted more CXCL16 and expressed higher CXCR6 compared to endometrial stromal cells (ESCs) in vitro . Stimulation with the inducer of decidualization (8-bromoadenosine 3′, 5′-cyclic with medroxyprogesterone acetate, 8-Br-cAMP plus MPA) significantly upregulated the expression of CXCL16 and CXCR6 in ESCs in vitro . After treatment with exogenous recombinant human CXCL16 (rhCXCL16) or trophoblast-secreted CXLC16, decidualised ESCs showed a significant decidual response, mainly characterised by increased prolactin (PRL) secretion. Simultaneously, PI3K/PDK1/AKT/Cyclin D1 pathway in decidualised ESCs were activated by rhCXCL16, and AKT inhibitor GS 690693 abolished the PRL secretion of ESCs that was triggered by rhCXCL16. Finally, the impaired CXCL16/CXCR6 expression could be observed at the maternal–foetal interface from patients who have experienced spontaneous abortion. This study suggests that the CXCL16/CXCR6 axis contributes to the progression of ESC decidualization by activating PI3K/PDK1/AKT/Cyclin D1 pathway. It unveils a new paradigm at the maternal–foetal interface in which CXCL16 is an initiator for the molecular crosstalk that enhances decidualization of ESCs.